2008
DOI: 10.1177/0032885508322492
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CCTV on Prisoner Misbehavior

Abstract: Despite the widespread use of closed circuit television (CCTV) in prison, few studies have explored its effect on prisoner misbehavior. Research was conducted to explore two research questions: (i) does CCTV have a greater preventative effect on nonviolent than violent prisoner misbehavior, and (ii) does CCTV have a greater preventative effect on planned than unplanned violent behavior. Data were obtained on the 1,116 incidents involving aberrant prisoner behavior that occurred at four prisons in Queensland (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…Given that recent research of public surveillance cameras suggest active monitoring is critical to the technology's effectiveness (La Vigne et al, 2011a), the absence of stronger effects may also be because of the lack of integrating these interventions with additional staff training, an accompanying inmate behavior management strategy or stronger monitoring. To be sure, cameras have been found to be effective in other studies (for example, Allard et al, 2008;La Vigne et al, 2011a), and it may be that the manner in which these cameras were deployed and used limited their effectiveness. Although the jail is credited with implementing mandatory video review for every incident and monthly random reviews of video footage, there was little direct monitoring of cameras and random reviews only covered a relatively small proportion of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that recent research of public surveillance cameras suggest active monitoring is critical to the technology's effectiveness (La Vigne et al, 2011a), the absence of stronger effects may also be because of the lack of integrating these interventions with additional staff training, an accompanying inmate behavior management strategy or stronger monitoring. To be sure, cameras have been found to be effective in other studies (for example, Allard et al, 2008;La Vigne et al, 2011a), and it may be that the manner in which these cameras were deployed and used limited their effectiveness. Although the jail is credited with implementing mandatory video review for every incident and monthly random reviews of video footage, there was little direct monitoring of cameras and random reviews only covered a relatively small proportion of time.…”
Section: Discussionmentioning
confidence: 99%
“…The first study to examine behavioral outcomes of CCTV in correctional environments was a survey of 220 inmates at a British prison for young offenders (see Allard et al, 2008). The study compared self-reported rates of victimization and offending between inmates living in units with CCTV in the shower areas and inmates living in units without cameras.…”
Section: Cctv In Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…U dosadašnjim istraživanjima otkrivene su izvesne pozitivne promene u ponašanju zatvorenika koje se mogu pripisati primeni video-nadzora. Kod osuđenika koji su boravili u prostorima pokrivenim video-nadzorom zabeleženo je i do 50% manje incidenata u odnosu na kontrolnu grupu (Allard et al, 2008). Isti autori nalaze da video-nadzor uspešnije prevenira nenasilne nego nasilne prestupe i planirane nasilne u odnosu na neplanirane nasilne postupke.…”
Section: Video-nadzor U Zatvorimaunclassified
“…A qualitative study of the implementation and impact of the program in six prisons found the approach to be promising, although more research is needed to determine its long-term impact on suicide and self-harm rates (Burrows et al 2003). Studies of the use of closed-circuit television cameras (CCTV) in Australian prisons found that the cameras did deter inmates from nonviolent misbehavior and planned acts of violence but not spontaneous violent acts such as fights (Allard et al 2008). In the 1990s, Rikers Island jails installed a computerized inmate phone system designed to save money and reduce illegitimate Evaluation of a Situational Crime Prevention Approach in Three Jails The Jail Sexual Assault Prevention Project 12 calls by inmates.…”
Section: A Situational Crime Prevention Approach To Addressing Violenmentioning
confidence: 99%